Sustainable leadership practices in construction: Building a resilient society - Ahsan Waqar; Moustafa Houda; Abdul Mateen Khan; Abdul Hannan Qureshi; Gremina Elmazi (Environmental Challenges, 2024)
While pivotal for economic growth, the global construction sector confronts critical challenges due to its resource-intensive practices and environmental impact. Leadership within this industry becomes essential as the imperative for sustainable development gains prominence. This study addresses a significant knowledge gap by investigating the nexus between sustainable leadership practices and the construction sector, focusing on Pakistan. A comprehensive framework is developed by combining literature review, expert analysis, and robust statistical methods. Data collection involved questionnaire involving 206 participants from construction industry professionals in Pakistan. The study examines the relation of green building design, certification standards, life cycle assessment, renewable energy integration, resilient infrastructure, social equity and inclusion, and waste management with sustainable leadership practices. The findings affirm the positive and significant relationships between these dimensions and sustainable leadership. The study contributes to academia and industry, offering a novel understanding of how sustainable leadership can drive resilient and eco-conscious practices in construction. These insights hold implications for shaping policies, fostering industry transformation, and creating a sustainable and resilient built environment for the future.